Trapped in the Virtual World: Excessive and Lonely Watching of Parasocial Interactions Among College Students - Aulia, Shalsha Anjani Putri; Suhesty, Aulia (UNIVERSITAS PAKUAN, 2025)
This study aims to determine the influence of excessive viewing and loneliness on parasocial interactions. This study uses a quantitative approach. The subjects of the study were 84 students of the Faculty of Dentistry Mulawarman who were selected using probability sampling techniques. The data collection methods used were the overviewing scale, the loneliness scale, and the parasocial interaction scale. The data analysis technique used is multiple linear regression. The collected data was analyzed with the help of the Statistical Package For Social Science (SPSS) version 21.0 for windows program. The results showed that: (1) there was an effect of the intensity of excessive watching use and loneliness on parasocial interaction with a value of F count = 93.459 F table = 3.11 and a P value = 0.000 and had an influence contribution (R2) of 69.8%. (2) there was a significant effect between excessive menonots and social interactions with the value of the beta coefficient (β) = 0.788, t count = 12.694 t table = 1.989 and p = 0.000 (p 0.005). (3) Then in loneliness with parasocial interactions, it shows t count t table which means that there is a significant influence with the value of the beta coefficient (β) = -0.171, t count = -2.754 t table = 1.989 and p = 0.007 (p 0.05). Further research may explore other factors that influence parasocial interactions, such as media type, intensity of social media use, or demographic characteristics.